On being the right (cell) size - Ginzberg, Miriam B.; Kafri, Ran; Krischner, Marc (Science (American Association for the Advancement of Science), 2015)
Biologists have long recognized that cells exist in a large range of sizes. Cell size is also flexible: Cells can differentiate into another cell type with a very different size. External factors can also influence cell size, but the consistent size of a given cell type shows that cells have mechanisms to measure their own size and adjust their growth rate or rate of cell division to maintain uniformity. Ginzberg et al. review recent advances in understanding how cells know when they are at the right size. Science , this issue 10.1126/science.1245075 Different animal cell types have distinctive and characteristic sizes. How a particular cell size is specified by differentiation programs and physiology remains one of the fundamental unknowns in cell biology. In this Review, we explore the evidence that individual cells autonomously sense and specify their own size. We discuss possible mechanisms by which size-sensing and size-specification may take place. Last, we explore the physiological implications of size control: Why is it important that particular cell types maintain a particular size? We develop these questions through examination of the current literature and pose the questions that we anticipate will guide this field in the upcoming years.